Thar Amrit: A new high-yielding custard apple variety for dryland - Yadav, Vikas; Singh, A K; Hiwale, S S; Singh, Sanjay; Sharma, B D (Indian Horticulture, 2023)
Thar Amrit variety of Custard apple is precocious, regular bearer, and starts bearing in 2nd year. It has fruit weight of 320.12 g, having high pulp content (63.58%), and can be used for both table and processed purpose owing to high fruit pulp TSS (29.12°Brix). It is drought hardy and capable to give stable economic yield during aberrant agro-climatic conditions (350 mm). Fruits emit strong aromaat full ripening stage. It belongs to late maturing group (2nd week of November) with high yield (24.80 kg/plant in 11th year) under rainfed semi-arid conditions of western India. The fruit is rich in ascorbic acid (45-50 mg), iron (1.70 mg), phosphorous (26.0 mg), potassium (285.55 mg) and calcium (18.21 mg) content. It is a heavy yielder, and fruit bearing occurs on lateral and terminal branches in this variety. It was developed at Central Horticultural Experiment Station, Godhra, Gujarat and identified and released at Institute level (ICAR-CIAH) in 2022.